An effect Microwave Assisted Extraction (MAE) of phenolic compounds from Java tea (Orthosiphon stamineus) - Muhammad Faiz Md Fauzi (2016)
Phenolic are largest group of secondary metabolites which widely distributed in plant kingdom. These polyphenols have drawn attention due to their strong beneficial properties such as antioxidant and their noticeable effect in prevention of various diseases such as cancer due to the oxidation stress. Hence, an efficient method of extraction to obtain high yield of phenolic was carried out. This study was conducted to determine an efficient microwave assisted extraction (MAE) of phenolic compounds from Java Tea (O.stamineus). The optimum MAE parameters such as solvent-type, solvent concentration (v/v, %), different extraction time (min), sample-solvent ratio (w/v), and different irradiation power (Watt) of microwave were identified to obtain high yield of Total phenloic content (TPC) from Java tea leaves. TPC of Java tea leaves with different parameters of extraction were estimated by using the Folin-ciocalteu (FC) assay and spectrophotometric method. Generally, high extraction yield was obtained by using 50% aqueous acetone as a solvent (516.45 GAE mg/g), 20 min of extraction time (350.89 GAE mg/g), 1:20 of sample-solvent ratio (w/v) (406.45 GAE mg/g), and 180 Watt of irradiation power of microwave (414.78 GAE mg/g). Further work will be required to identify other parameters that will also can be major effect on the yield of TPC inside the Java Tea such as sample weight ratio, different part of plant, form of the sample (powder or piece) and etc.